2019
DOI: 10.1111/camh.12348
|View full text |Cite
|
Sign up to set email alerts
|

Examining parent and child agreement in the diagnosis of adolescent depression

Abstract: Background The diagnosis of depression in adolescents relies on identifying the presence of specific core and additional symptoms. Symptoms can be identified using structured or unstructured interviews and a range of questionnaire measures, which are completed by the young person and by a parent or carer. The aim of this research was to examine the inter‐ and intra‐rater reliability of parent report and adolescent self‐report of depression symptoms. Method In a sample of parent–child dyads, where young people … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 36 publications
2
27
1
Order By: Relevance
“…YES is a non-randomized, exploratory program evaluation; procedures and analyses were preregistered on Open Science Framework [ 50 ]. In order to maintain anonymity and minimize access barriers (eg, discomfort disclosing psychological distress, as parents are often unaware of their adolescents’ depressive symptoms, including suicidal and morbid ideation, in up to 80% of cases [ 51 , 52 ]), parent permission is not required to participate (waived by the University IRB). After clicking the YES participation link and advancing past a “Project Information” page where agreement to participate is indicated, participants provide non-identifying demographic information; select one of three SSIs to complete; and may then complete pre-SSI questionnaires, the SSI, and post-SSI questionnaires, designed to gauge the SSI’s acceptability and short-term effects.…”
Section: Methodsmentioning
confidence: 99%
“…YES is a non-randomized, exploratory program evaluation; procedures and analyses were preregistered on Open Science Framework [ 50 ]. In order to maintain anonymity and minimize access barriers (eg, discomfort disclosing psychological distress, as parents are often unaware of their adolescents’ depressive symptoms, including suicidal and morbid ideation, in up to 80% of cases [ 51 , 52 ]), parent permission is not required to participate (waived by the University IRB). After clicking the YES participation link and advancing past a “Project Information” page where agreement to participate is indicated, participants provide non-identifying demographic information; select one of three SSIs to complete; and may then complete pre-SSI questionnaires, the SSI, and post-SSI questionnaires, designed to gauge the SSI’s acceptability and short-term effects.…”
Section: Methodsmentioning
confidence: 99%
“…Adolescent reported outcomes were prioritised for two reasons. First these data were more often available than symptom reports from parents; second, there is evidence of significant discrepancy between adolescent and parent reports of the young person's symptoms, meaning that these cannot be considered inter-changeable (Orchard, Pass, Cocks, Chessell, & Reynolds, 2019).…”
Section: Data Synthesismentioning
confidence: 99%
“…This is consistent with previous research showing that parental proxy-report identifies depressive symptoms less frequently than their child’s self-report ( Eg et al, 2018 ; Orchard et al, 2017 ). Higher agreement has been demonstrated for externalising behaviours ( Comer & Kendall, 2004 ; Hemmingsson et al, 2017 ; Orchard et al, 2019 ), which are often directly observable or occur in the home environment. This is true for both mental and physical health parameters.…”
Section: Introductionmentioning
confidence: 98%
“…One large meta-analysis of 341 studies demonstrated only low to moderate correlations between children and parents in relation to mental health symptoms ( De Los Reyes et al, 2015 ). Recent evidence evaluating depression found that parents identified fewer symptoms than their adolescent children, meaning adolescents met the diagnostic criteria less frequently based on parental responses ( Orchard et al, 2019 ). This is consistent with previous research showing that parental proxy-report identifies depressive symptoms less frequently than their child’s self-report ( Eg et al, 2018 ; Orchard et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%